2016
DOI: 10.3389/fenvs.2016.00057
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Electrochemical Processes with Membrane Bioreactors for Wastewater Treatment and Fouling Control: A Review

Abstract: This paper provides a critical review about the integration of electrochemical processes into membrane bioreactors (MBR) in order to understand the influence of these processes on wastewater treatment performance and membrane fouling control. The integration can be realized either in an internal or an external configuration. Electrically enhanced membrane bioreactors or electro membrane bioreactors (eMBRs) combine biodegradation, electrochemical and membrane filtration processes into one system providing highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 60 publications
0
28
0
3
Order By: Relevance
“…In activated sludge process, the solids/liquid separation typically takes place through a separation of spontaneously aggregated flocs by gravity sedimentation in secondary clarifiers 1 , while in membrane bioreactors, the biosolids are separated by means of a polymeric membrane based on microfiltration or ultrafiltration 2 . The integration of electrochemical processes into wastewater treatment bioreactors combine biodegradation, electrochemical, and sludge separation processes into one system, achieving high effluent quality when compared to conventional process 3 5 . Current density (CD) is a crucial factor which affects the performance of electrochemical treatment in electrically enhanced wastewater treatment bioreactors, controlling the dosing rate of metal ions and the gas bubble density that are released in the solution via redox reactions of electrodes 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In activated sludge process, the solids/liquid separation typically takes place through a separation of spontaneously aggregated flocs by gravity sedimentation in secondary clarifiers 1 , while in membrane bioreactors, the biosolids are separated by means of a polymeric membrane based on microfiltration or ultrafiltration 2 . The integration of electrochemical processes into wastewater treatment bioreactors combine biodegradation, electrochemical, and sludge separation processes into one system, achieving high effluent quality when compared to conventional process 3 5 . Current density (CD) is a crucial factor which affects the performance of electrochemical treatment in electrically enhanced wastewater treatment bioreactors, controlling the dosing rate of metal ions and the gas bubble density that are released in the solution via redox reactions of electrodes 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The integration of electrochemical processes into membrane bioreactors (MBRs) combines biodegradation, electrochemical and membrane filtration processes into one system achieving high effluent quality as compared to conventional MBRs and activated sludge processes (Ensano et al, 2016). New and cheaper developments have suggested that the continuous and intermittent application of a direct current (DC) field has proven to enhance membrane filterability and is similarly effective in controlling membrane fouling (Akamatsu, Lu, Sugawara, & Nakao, 2010;Akamatsu et al, 2012;Liu, Liu, Gao, & Yang, 2012;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the interactions between aluminium and phosphate ions inside the reactor which resulted in the significant removal of the latter from the solution [57]. Aside from adsorption onto Al(OH) 3 coagulants, excess aluminium ions (Al 3+ ) react with phosphorous ions to form (AlOH) 3 (PO 4 ) 2 (s) and AlPO 4 (s) that precipitate out in the bioreactor according to the following reactions (Equations (7) and (8)) [58]:…”
Section: Removal Of Conventional Pollutantsmentioning
confidence: 99%